2018
DOI: 10.1186/s40623-018-0807-7
|View full text |Cite
|
Sign up to set email alerts
|

Geoelectric hazard assessment: the differences of geoelectric responses during magnetic storms within common physiographic zones

Abstract: Geomagnetic field data obtained through the INTERMAGNET program are convolved with with magnetotelluric surface impedance from four EarthScope USArray sites to estimate the geoelectric variations throughout the duration of a magnetic storm. A duration of time from June 22, 2016, to June 25, 2016, is considered which encompasses a magnetic storm of moderate size recorded at the Brandon, Manitoba and Fredericksburg, Virginia magnetic observatories over 3 days. Two impedance sites were chosen in each case which r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…Those developed for North America (Blum et al, ; Fernberg, ; Ferguson & Odwar, ) have been used to estimate benchmarks for NERC and in numerous related studies (e.g., Marti et al, ; Nikitina et al, ; Ngwira et al, ; Pulkkinen et al, ; Trichtchenko et al, ; Wei et al, ); indeed, 1‐D models are sometimes treated as first‐order representations of the Earth (e.g., Boteler, ; Butala et al, ; Gannon et al, ; Marti et al, ). Despite this, several studies have shown that the use of some 1‐D models (e.g., Fernberg, ) can give estimated geoelectric amplitudes that are erroneous by more than an order of magnitude (in some cases, the error exceeds 2 orders of magnitude; e.g., Bedrosian & Love, ; Cuttler et al, ; Love, Rigler, et al, ; Lucas et al, ). Furthermore, the magnetotelluric community routinely uses measured impedance tensors, such as those summarized in Figure , to construct regional models of subsurface electrical conductivity structure that are far from 1‐D, including for the Pacific Northwest (e.g., Bedrosian & Feucht, ; Meqbel et al, ; Patro & Egbert, ).…”
Section: Magnetotelluric Impedance Tensorsmentioning
confidence: 99%
“…Those developed for North America (Blum et al, ; Fernberg, ; Ferguson & Odwar, ) have been used to estimate benchmarks for NERC and in numerous related studies (e.g., Marti et al, ; Nikitina et al, ; Ngwira et al, ; Pulkkinen et al, ; Trichtchenko et al, ; Wei et al, ); indeed, 1‐D models are sometimes treated as first‐order representations of the Earth (e.g., Boteler, ; Butala et al, ; Gannon et al, ; Marti et al, ). Despite this, several studies have shown that the use of some 1‐D models (e.g., Fernberg, ) can give estimated geoelectric amplitudes that are erroneous by more than an order of magnitude (in some cases, the error exceeds 2 orders of magnitude; e.g., Bedrosian & Love, ; Cuttler et al, ; Love, Rigler, et al, ; Lucas et al, ). Furthermore, the magnetotelluric community routinely uses measured impedance tensors, such as those summarized in Figure , to construct regional models of subsurface electrical conductivity structure that are far from 1‐D, including for the Pacific Northwest (e.g., Bedrosian & Feucht, ; Meqbel et al, ; Patro & Egbert, ).…”
Section: Magnetotelluric Impedance Tensorsmentioning
confidence: 99%
“…The 1‐D conductivity models of Fernberg () and the USArray 3‐D impedance tensors available from the Incorporated Research Institutions for Seismology (IRIS) Searchable Product Depository (http://ds.iris.edu/spud/emtf) provide impedance information for large regions across the contiguous United States. Several recent studies have utilized both the 1‐D and 3‐D impedance tensors in the calculation of the surface electric field for purposes of space weather threat assessment (Bedrosian & Love, ; Bonner & Schultz, ; Butala et al, ; Cuttler et al, ; Gannon et al, ; Love et al, , , ; Lucas et al, ; Weigel, ).…”
Section: Introductionmentioning
confidence: 99%
“…From this study, we learn that E3 EMP geoelectric fields, generated by a nuclear explosion in the near-Earth space environment above our heads, can be strongly affected by the geography of the Earth's surface impedance, a tensor that is a function of threedimensional geological structures beneath our feet. This qualitative point might have been anticipated from previous analyses in which synthetic magnetic signals [e.g., Bedrosian and Love, 2015;McKay and Whaler , 2006] and measured magnetic-storm variation [e.g., Cuttler et al, 2018;Kelbert et al, 2017;Lucas et al, 2018] are convolved with long-period (< 10 −1 Hz; > 10 s) magnetotelluric impedance tensors. Local surface impedance can have a significant effect on the amplitude, polarization, and variational phase of local induced geoelectric fields.…”
Section: Conclusion and Discussionmentioning
confidence: 72%